Modeling Groundwater Potential Zones across Sulaimani Governorate Using Geographic Information System and Multi-influencing Factor Techniques - Rashid, Haveen Muhammed (UHD Journal of Science and Technology, 2021)
Groundwater is one of the most important natural resources in the world. The presence of groundwater is the result of interaction of several factors such as: hydrology, geology, climate, ecology, and physiography. The purpose of this paper is to produce groundwater potential zones which are useful in determining the amount of groundwater available in Sulaimani Governorate, North of Iraq. Geographic information system database for six different thematic layers (digital elevation model, rainfall, soil texture, drainage density, slope and land use/land cover) were generated. The study approach involved integration of six layers carried out based on the multiplication of each data raster values with specific weight using weighted overlay analysis method. Raster maps of all the layers assigned a fixed score and weight using multi-influencing factor technique. Based on the resulted map the study area has been divided into four zones that had very high potential zone (1%), high potential zone (14%), moderate zone potential (79%) and low potential zone (6%). About 50% of the high groundwater potential zone were located in Halabja, Rania, and Pshdar districts. Obtained results can be useful in localizing areas of exploration, preventing excessive exploitation of groundwater and planning for suitable sites of artificial groundwater.